MicroRNA-124-3p Plays a Crucial Role in Cleft Palate Induced by Retinoic Acid - Yoshioka, Hiroki; Mikami, Yurie; Ramakrishnan, Sai Shankar; Suzuki, Akiko; Iwata, Junichi (Frontiers in Cell and Developmental Biology, 2021)
Cleft lip with/without cleft palate (CL/P) is one of the most common congenital birth defects, showing the complexity of both genetic and environmental contributions [e.g. maternal exposure to alcohol, cigarette, and retinoic acid (RA)] in humans. Recent studies suggest that epigenetic factors, including microRNAs (miRs), are altered by various environmental factors. In this study, to investigate whether and how miRs are involved in cleft palate (CP) induced by excessive intake of all-trans RA (atRA), we evaluated top 10 candidate miRs, which were selected through our bioinformatic analyses, in mouse embryonic palatal mesenchymal (MEPM) cells as well as in mouse embryos treated with atRA. Among them, overexpression of miR-27a-3p, miR-27b-3p, and miR-124-3p resulted in significant reduction of cell proliferation in MEPM cells through downregulation of CP-associated genes. Notably, we found that excessive atRA upregulated expression of miR-124-3p, but not of miR-27a-3p and miR-27b-3p, in both in vivo and in vitro. Importantly, treatment with a specific inhibitor for miR-124-3p restored decreased cell proliferation through normalization of target gene expression in atRA-treated MEPM cells and atRA-exposed mouse embryos, resulting in the rescue of CP in mice. Taken together, our results indicate that atRA causes CP through the induction of miR-124-3p in mice.